Psoriasis and Coxsackie. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. We followed for a long a patient of 50 years suffering from widespread psoriasis patches. The brother and the father had psoriasis. He regularly underwent depressive episodes. Five months before a neoformation arisen on a psoriatic patch of the perianal region was removed and the histological examination showed verrucous carcinoma. 12 days before our latest observation the 3 year old daughter had a classical form of hand-foot and mouth disease. 5 days later the patient presented fever, burning sore throat and vesicular lesions localized on the hands, feet and buttocks and prevailing on the psoriatic patches; the lesions of the feet prevented him to walk for two days and those of the buttocks made it impossible to sit. When we observed him 4 days after the onset of fever, the disease was already improving. The physical examination revealed a vesicular eruption localized on the palmar and plantar region and especially lower limbs, localized almost exclusively on previous psoriatic lesions (Fig. 1, 2, 3, 4); there were elongated vesicles in the palms and soles and rounded, vesicular, eroded and crusted lesions in other sites; there were not evident lesions in the oral cavity. The final diagnosis was hand-foot and mouth disease prevailing on plaque psoriasis.